2008
DOI: 10.1111/j.1469-8749.2008.03096.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept in children with spina bifida compared with typically developing children

Abstract: The literature was systematically reviewed to determine if children with spina bifida have lower self-concept compared with their peers with typical development. Relevant trials were identified by searching electronic databases, supplemented by citation tracking. Of 803 papers initially identified, 15 met the inclusion criteria. Meta-analysis revealed children with spina bifida scored significantly lower than children with typical development for the domains of global self-worth (d=)0.39, 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 18 publications
(135 reference statements)
3
23
0
1
Order By: Relevance
“…For example, in a metanalysis, Shields et al [12] considered seven studies of young people with spina bifida and report that they show significant lower scores than healthy peers in the domains of global self-worth, physical appearance, athletic competence, social acceptance, and scholastic competence. Similarly, in a recent metanalytic comparison of children and adolescents with chronic illness, Pinquart [13] reported that young people with a chronic illness had a less positive body image than their healthy peers, although the average size of differences was small.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a metanalysis, Shields et al [12] considered seven studies of young people with spina bifida and report that they show significant lower scores than healthy peers in the domains of global self-worth, physical appearance, athletic competence, social acceptance, and scholastic competence. Similarly, in a recent metanalytic comparison of children and adolescents with chronic illness, Pinquart [13] reported that young people with a chronic illness had a less positive body image than their healthy peers, although the average size of differences was small.…”
Section: Discussionmentioning
confidence: 99%
“…To Campell (1990), self concept and self esteem in adolescents are closely related to such factors as academic success, sportive performance, drug addiction, early pregnancy, the quality of communication with peers and acquisition of specific coping skills (quoted by Aktuğ, 2006). It was explored in literature that individuals who need special education have lower self concept than normal individuals (Shields et al, 2006;Korkmaz, 2007;Shields et al, 2008). We can suggest that it is both socially and individually important to attempt to increase self concept of the children with mild mental disability through various instruments or that they have high self concept as in children or adolescents with normal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Four criteria (Table 1) were adapted from the STROBE quality appraisal checklist 37 and risk of bias assessment tools specific to observational 38 and prevalence studies 39 , being selection and response bias, use of valid and reliable outcome measures, and interpretation bias. Two authors (VT and SP) independently assessed studies for risk of bias as high, low or uncertain.…”
Section: Risk Of Bias Assessment and Quality Appraisalmentioning
confidence: 99%
“…Screening the reference lists of the remaining 76 papers yielded one further potentially eligible paper. Full text assessment led to the exclusion of 62 papers, reasons being that they did not include or separately report 12-22year old participants' data (38) or data for those with NMD (9), did not include or describe participants' ambulatory status (9), reported proxyrated outcomes only (5) or could not be sourced (1). All authors reached consensus for the 15 papers that met the inclusion criteria.…”
Section: Study Selectionmentioning
confidence: 99%